2020
DOI: 10.2196/22596
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Mental Health and Personal Preventive Measure Compliance With Exposure to COVID-19 Information During Work Resumption Following the COVID-19 Outbreak in China: Cross-Sectional Survey Study

Abstract: Background Risk and crisis communication plays an essential role in public health emergency responses. The COVID-19 pandemic has triggered spontaneous and intensive media attention, which has affected people’s adoption of personal preventive measures and their mental health. Objective The aim of this study was to investigate the associations between exposure to COVID-19–specific information and mental health (depression and sleep quality) and self-repor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 42 publications
(57 reference statements)
6
76
0
1
Order By: Relevance
“…Regarding vaccination uptake, women in the United Kingdom who used social media to gather information reported lower pertussis vaccination uptake during pregnancy [46], while positive associations between information exposure through social media and vaccination were found among White and African American adults in the United States [40] and older adults in China [47]. Moreover, different contents related to COVID-19 may have varying effects on personal preventive measures [48]. In this study, we investigated the associations between exposure to different content related to COVID-19 vaccination on social media and behavioral intention to receive a vaccination.…”
Section: Development Of the Covid-19 Vaccines Is On The Waymentioning
confidence: 99%
“…Regarding vaccination uptake, women in the United Kingdom who used social media to gather information reported lower pertussis vaccination uptake during pregnancy [46], while positive associations between information exposure through social media and vaccination were found among White and African American adults in the United States [40] and older adults in China [47]. Moreover, different contents related to COVID-19 may have varying effects on personal preventive measures [48]. In this study, we investigated the associations between exposure to different content related to COVID-19 vaccination on social media and behavioral intention to receive a vaccination.…”
Section: Development Of the Covid-19 Vaccines Is On The Waymentioning
confidence: 99%
“…Higher prevalence of anxiety and depressive symptoms are found among people less than 35 years old, health professionals that spent more than 3 hours/day during the pandemic, have poor sleep quality in comparison with other occupations. 7 In another study, poor knowledge, lack of training, and inadequacy of personal protective equipment lead to severe distress among health professionals, 8,9 with this condition weakening their immune systems, as studies found higher infection rates in practitioners' well-being. 10 Furthermore, in developing mental health policy, it is very important to consider all psychological well-being issues arising in the community, including, stigmatization discrimination…”
Section: Introductionmentioning
confidence: 99%
“…Avoiding information entirely was a significant predictor of health anxiety symptoms, with higher levels of avoidance positively associated with health anxiety symptoms. For Hypothesis 1, where three separate regressions were used to investigate associations between sources of information and symptoms of psychopathology, the strongest effect sizes were found for using social media and newspapers to obtain information about COVID-19, and these findings align with other pandemic findings, indicating that obtaining news about COVID-19 using different media is associated with psychological distress (Bendau et al, 2020;Pan et al, 2020). Support was not found for the hypothesized associations for TV, forums and blogs, friends and family and other sources.…”
Section: Information Seeking Behaviour and Symptoms Of Health Anxietymentioning
confidence: 65%